Акклиматизация мозоленогих (Tylopoda) в Аскании-Нова - Треус, В.Д.; Лобанов, Н.В. (Вестник зоологии, 1976)
In 1902-1972 in Askania Nova 110 of Lama guanicoè, L. g. glama and their hybrids were obtained in offspring. The season of giving birth to the young falls on April- August (80%). The longest lifetime is 18 years. The females are mature at the age of three year, the males-somewhat later. The gestation period of L. g. glama is 365+25 days, and that of L. g. guanicoè 315 15 days. In the experiments on artificial insemina- tion of Camelus dromedarius and C. bactrianus females with sperm of L. g. guanicoè no hybrid embryos were observed.